(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2022)
This study explores how influencer credibility and brand–influencer fit affect purchase intention among Generation Z consumers in Bandung, Indonesia. As influencer marketing are currently rapidly mature, the alignment between brand identity and influencer persona became a crucial determinant of marketing effectiveness. Drawing from the source credibility theory and the match-up hypothesis, this research investigates whether credible and well-matched influencers strengthen consumers’ willingness to purchase. Data were collected from 180 active social-media users from Generation Z who follow cosmetic brands promoted by Indonesian influencers. Using multiple linear regression, results reveal that both influencer credibility and brand–influencer fit have a significant positive effect on purchase intention (p < 0.05). These findings confirm that trustworthiness and congruence enhance persuasive impact. The findings highlight the importance for marketers to select influencers not only based on popularity but on authenticity and value alignment to sustain consumer engagement and conversion